Tingkat Kebugaran Jasmani Siswa Usia 6-9 Tahun SDN 67 Palembang Tahun Pelajaran 2019/2020 - Anes Winarti ningsih; Taufikur Rohman; Pur nawan; Herwan syah; Sutris no (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2023)
This study aims to determine the level of physical fitness of students aged 6-9 years at SDN 67 Palembang for the 2019/2020 academic year. The approach used in this research is quantitative. The population of this study was students of class I-III SDN 67 Palembang while the sample used was 86 students aged 6-9 years. Measurement of the Indonesian Physical Freshness Test was carried out by measuring 5 items, namely running 30 meters, hanging elbows, lying down, jumping upright, and running 600 meters. The results showed that 64 students (74%) were categorized as having less physical fitness, 20 students (24%) categorized as having moderate physical fitness, and 2 students (2%) were categorized as having very poor physical fitness. The results of this study can be concluded that the level of physical fitness of students aged 6-9 years at SDN 67 Palembang for the 2019/2020 academic year is in the low category. Keywords: Physical fitness, student, low category